Mamasab International Sdn. Bhd. / Nurul Natasya Harun - Harun, Nurul Natasya (2021)
This report contains the social media post on Facebook. There is a teaser of the product, the soft sell and hard sell that was already posted on Facebook. This is to attract buyers to buy the product with the beginning that is teaser followed by soft sell to attract more customers and hard sell more useful to tell the importance of our product so that we can convince customers to buy the product. Using social media marketing, there is a lot of demand in the product especially when the media is used by various types of the groups from gender, age and so on. By using social media such as Facebook, Instagram, Twitter and so on, the seller can get a lot of attention or demand from customers because they know the product exists. The customers also can get benefits by buying from online sellers. They can be frugal in various factors and they will also know more about the importance or benefits of a product by asking directly to the seller.